Measurement of the association between perceived exercise capability and childhood obesity: a feasibility study. (13th November 2015) - Taylor, Michael James; Arriscado, Daniel; Vlaev, Ivo; Taylor, David; Gately, Paul; Darzi, Ara
Abstract: Background: According to the COM-B model of behaviour, three factors are essential for behaviour to occur: capability, opportunity, and motivation. Some evidence suggests that obese children tend to feel less capable of exercising. An instrument aiming to measure perceived exercise capability, opportunity, and motivation was created and subsequently used to investigate the association between perceived exercise capability and childhood obesity, and how perceived exercise capability could be improved through intervention. Methods: A 19 item questionnaire about exercise capability, opportunity, and motivation was created systematically with the COM-B model. On arrival at a 6 week weight-management camp in northern England, children completed the questionnaire; Spanish schoolchildren attending after-school exercise sessions in Spain also completed the questionnaire to test generalisability of findings. Motion-sensor computer games were implemented at weekly sessions at the English weight-management camp to encourage exercise and improve attendees' perceived exercise capability. No participants withdrew from the study. Linear regression was used to investigate associations between body-mass index SD scores (BMI SDS) and perceived exercise capability, opportunity, and motivation; confirmatory factor analysis was conducted to investigate scale construct validity; Cronbach's α tests were conducted to measure internal consistency. Informed consent was obtained from all children, and from their parents or guardians. Ethics approval was granted by the Imperial College Research Ethics Committee and the Ethics Committee for Clinical Research, University of La Rioja. Findings: On arrival at the camp, questionnaires were completed by 71 English children (34 girls, 48%) aged 9–17 years (mean 12·2, SD 2·0) with BMI SDS 2·80 (SD 0·66) and by 45 Spanish schoolchildren (22 girls, 49%) aged 9–13 years (mean 10·5, SD 1·2) with mean BMI SDS 0·80 (SD 0·99). 22 attendees of the English camp (12 girls, 55%) aged 9–16 years (mean 12·1, SD 2·2) reported how much they enjoyed the games; and they completed the COM-B questionnaire on both arrival at, and departure from, the camp. Questionnaire composite capability, opportunity, and motivation scores tested adequately for internal consistency (Cronbach's α=0·712–0·796) and construct validity (χ 2 /df=1·55, root mean square error of approximation 0·072, comparative fit index 0·92). Linear regression revealed an inverse association between perceived exercise capability and BMI SDS for both English (β=–0·289, p=0·010) and Spanish (β=–0·446, p=0·047) children; no association between BMI SDS and perceived exercise opportunity or motivation was found. A positive correlation was found between extent of motion-sensor game enjoyment and improvement in perceived exercise capability ( r (22)=0·538, p=0·010), but not opportunity or motivation improvement, during stays at the camp. Interpretation: Perceived exercise capability can be measured with the instrument described here. This small-sample study provides preliminary evidence for an association between low perceived exercise capability and childhood obesity and for the possibility that perceived exercise capability can be improved through intervention. Funding: This research was supported by the Engineering and Physical Sciences Research Council (grant EP/K012673/1).